PENGEMBANGAN MODEL PEMBELAJARAN GERAK BERIRAMA “PAKEM” PADA SISWA SEKOLAH DASAR NEGERI DI KABUPATEN MAGELANG - Ahmad Sahid Insyagi; Roas Irsyada (Universitas Hamzanwadi, 2026)
The teaching of rhythmic movement in Physical Education (PJOK) at elementary schools still faces challenges in the form of low student engagement and a lack of variety in teaching strategies, resulting in suboptimal learning outcomes. This study aims to develop a PAKEM-based (Active, Creative, Effective, and Enjoyable) rhythmic movement learning model and to test its effectiveness in improving students’ learning processes and outcomes. The method used was Research and Development (R&D) employing the ADDIE model through the stages of analysis, design, development, implementation, and evaluation. The pilot study was conducted at SDN Giripurno 1, Magelang Regency, involving 23 students in the small-scale trial and 37 students in the large-scale trial. The results of the small-scale pilot test showed achievement percentages of 79% for psychomotor skills, 74% for cognitive skills, and 80% for affective skills. In the large-scale pilot test, the results were 76% for psychomotor skills, 70% for cognitive skills, and 81% for affective skills. The N-Gain test increased from 0.68 (moderate) to 0.72 (high), and the t-test revealed a significant difference between the pretest and posttest (p < 0.05). In conclusion, the PAKEM-based rhythmic movement learning model is deemed highly feasible and effective in enhancing student participation and learning outcomes in Physical Education (PJOK) instruction at the elementary school level.